Detection of Shiga toxin-producing Escherichia coli in ground beef using the GeneDisc real-time PCR system - Fratamico, Pina; Bagi, Lori K. (Frontiers in Cellular and Infection Microbiology, 2012)
Escherichia coli O157:H7 and certain non-O157 Shiga toxin-producing Escherichia coli (STEC) serogroups have emerged as important public health threats. The development of methods for rapid and reliable detection of this heterogeneous group of pathogens has been challenging. GeneDisc real-time PCR assays were evaluated for detection of the stx1, stx2, eae, and ehx genes and a gene that identifies the O157 serogroup followed by a second GeneDisc assay targeting serogroup-specific genes of STEC O26, O45, O91, O103, O111, O113, O121, O145, and O157. The ability to detect the STEC serogroups in ground beef samples artificially inoculated at a level of ca. 2-20 CFU/25 g and subjected to enrichment in mTSB or BPW was similar. Following enrichment, all inoculated ground beef samples showed amplification of the correct set of target genes carried by each strain. Samples inoculated with STEC serogroups O26, O45, O103, O111, O121, O145, and O157 were subjected to immunomagnetic separation, and isolation was achieved by plating onto Rainbow agar O157. Colonies were confirmed by PCR assays targeting stx1, stx2, eae, and serogroup-specific genes. Thus, this work demonstrated that GeneDisc assays are rapid, sensitive, and reliable and can be used for screening ground beef and potentially other foods for STEC serogroups that are important food-borne pathogens worldwide.